An Improved Mathematical Model Applying Practicable Algorithms - Tanveer Ahmad Tarray; Zahoor Ahmad Ganie; Baziga Youssuf (Yayasan Ahmar Cendekia Indonesia, 2019)
In this article, we have considered the problem of estimation of population variance on two occasion successive sampling. A class of estimators of population variance has been proposed and its asymptotic properties have been discussed. The proposed class of estimators is compared with the sample variance estimator when there is no matching from the previous occasion. Numerical illustrations are also given in support of the present study.